Tuning flexural elastic wave propagation in electroactive phononic crystals - Zhou, Xiaoling (2019)
In this paper, we investigate the flexural elastic wave propagation properties in phononic crystals (PCs) consisting of co-axial steel and electrorheological (ER) elastomer pillars deposited on a thin plate. The finite element method and the super cell technique are used to calculate the band structures and transmission spectra. It is found that the band gap boundaries of the PCs can be tuned by applying an electric field to the ER elastomer component. The relationship between the band gap boundaries and the electric field is given. It is also found that point and line defects can be created by properly applying an electric field to some of the cells. These defects bring defect bands inside the original band gaps and lead to elastic wave confinement in the point defect or along the line defect. The dependence of the defect band frequencies on the electric field is expounded. Band gap tunability, wave confinement, and wave guiding achieved by applying electric field in this paper are useful in applications of flexural vibration reduction and energy harvesting in engineering.